Model Autoregressive Integrated Moving Average (Arima) dalam Meramalkan Perkembangan Ijarah di Bank Umum Syariah - Eva Trisnawati Trisnawati (Program Pascasarjana STIE Amkop Makassar, 2022)
Ijarah as one of the outputs of Islamic banks is starting to get public attention. Ijarah is the transfer of use of goods and services for a certain period of time through the transfer of ownership of goods. The aim is to predict the development of Ijarah in Islamic Commercial Banks using the Autoregressive Integrated Moving Average (ARIMA) Model. Time series analysis is an analysis commonly used to model time series data. This analysis can be used using preliminary data to predict the future of Ijarah. The Autoregressive Integrated Moving Average (ARIMA) model is a time series model that can be used to model Ijarah. The resulting balance in the ARIMA model will help predict the next phase of Ijarah. In this study, Ijarah data was used from January 2018 to Ijarah data in December 2020. The results showed that the ARIMA model for forecasting Ijarah during 2021 was successfully implemented. Results Based on Forecasting on Ijarah financing shows a drastic decline until the end of 2021. Anticipating the results of ijarah forecasting during 2021 which tend to decline, Islamic commercial banks need to implement strategies to be more aggressive in implementing education and innovation in financing products. Ijarah growth must be supported by the Government's persistence in campaigning for Islamic banks.